Biological Evaluation of Naproxen–Dehydrodipeptide Conjugates with Self-Hydrogelation Capacity as Dual LOX/COX Inhibitors - Moreira, Rute (Pharmaceutics, 2020)
The use of peptide–drug conjugates is emerging as a powerful strategy for targeted drug delivery. Previously, we have found that peptides conjugated to a non-steroidal anti-inflammatory drug (NSAID), more specifically naproxen–dehydrodipeptide conjugates, readily form nanostructured fibrilar supramolecular hydrogels. These hydrogels were revealed as efficacious nano-carriers for drug delivery applications. Moreover, the incorporation of superparamagnetic iron oxide nanoparticles (SPIONs) rendered the hydrogels responsive to external magnetic fields, undergoing gel-to-solution phase transition upon remote magnetic excitation. Thus, magnetic dehydrodipeptide-based hydrogels may find interesting applications as responsive Magnetic Resonance Imaging (MRI) contrast agents and for magnetic hyperthermia-triggered drug-release applications. Supramolecular hydrogels where the hydrogelator molecule is endowed with intrinsic pharmacological properties can potentially fulfill a dual function in drug delivery systems as (passive) nanocariers for incorporated drugs and as active drugs themselves. In this present study, we investigated the pharmacological activities of a panel of naproxen–dehydrodipeptide conjugates, previously studied for their hydrogelation ability and as nanocarriers for drug-delivery applications. A focused library of dehydrodipeptides, containing N-terminal canonical amino acids (Phe, Tyr, Trp, Ala, Asp, Lys, Met) N-capped with naproxen and linked to a C-terminal dehydroaminoacid (ΔPhe, ΔAbu), were evaluated for their anti-inflammatory and anti-cancer activities, as well as for their cytotoxicity to non-cancer cells, using a variety of enzymatic and cellular assays. All compounds except one were able to significantly inhibit lipoxygenase (LOX) enzyme at a similar level to naproxen. One of the compounds 4 was able to inhibit the cyclooxygenase-2 (COX-2) to a greater extent than naproxen, without inhibiting cyclooxygenase-1 (COX-1), and therefore is a potential lead in the search for selective COX-2 inhibitors. This hydrogelator is a potential candidate for dual COX/LOX inhibition as an optimised strategy for treating inflammatory conditions.